Pengaruh Jenis Variasi Perekat pada Briket dari Limbah Ampas Kopi - Edwin Eka Crisdiantoro; Mohammad Prasanto Bimantio; Herawati Oktavianty (Program Studi Teknologi Hasil Pertanian, 2024)
The depletion of conventional energy sources has prompted the exploration of alternative energy materials, one of which is coffee grounds. Coffee grounds can be processed into briquettes, a solid fuel with high carbon content, high calorific value, and prolonged combustion duration, making them a viable alternative energy solution. This study aims to determine whether the type and proportion of binder significantly affect the briquette properties and to identify the most effective binder for briquette production. The research utilizes an experimental design with a Complete Randomized Block Design (CRBD) consisting of two factors, with two replications. The binders used in this study are starch and arpus, with binder concentrations of 12%, 16%, and 20%. The briquettes were evaluated based on several parameters, including moisture content, volatile matter content, ash content, fixed carbon content, calorific value, and burning rate. The results indicate that binder type (Factor A) significantly affects all tested parameters, and binder proportion (Factor B) also influences the same parameters. The best moisture content was observed in the A2B1 treatment, which used arpus as a binder with a 12% proportion, resulting in an average moisture content of 4.72%. The lowest ash content was found in the A2B3 treatment (arpus binder, 20% proportion), with an average ash content of 4.31%. The highest calorific value was recorded in the A2B1 treatment (arpus binder, 12% proportion), with an average calorific value of 6334.03 cal/g. The best burning rate was found in the A2B3 treatment (arpus binder, 20% proportion), with an average burning rate of 51.83 mg/s. These findings suggest that arpus is an effective binder for coffee ground briquettes, with optimal performance achieved at specific binder proportions depending on the desired properties.